Epidemiological evidence relating risk factors to chronic obstructive pulmonary disease in China: A systematic review and meta-analysis. - Hong Chen; Xiang Liu; Xiang Gao; Yipeng Lv; Liang Zhou; Jianwei Shi; Wei Wei; Jiaoling Huang; Lijia Deng; Zhaoxin Wang; Ying Jin; Wenya Yu (PLoS ONE)
Background Chronic obstructive pulmonary disease (COPD), the most common chronic respiratory disease worldwide, not only leads to the decline of pulmonary function and quality of life consecutively, but also has become a major economic burden on individuals, families, and society in China. The purpose of this meta-analysis was to explore the risk factors for developing COPD in the Chinese population that resides in China and to provide a theoretical basis for the early prevention of COPD. Methods A total of 2457 cross-sectional, case-control, and cohort studies published related to risk factors for COPD in China were searched. Based on the inclusion and exclusion criteria, 20 articles were selected. Stata 11.0 was used for meta-analysis. After merging the data, the pooled effect and 95% confidence intervals (CIs) were calculated to assess the association between risk factors and COPD. Heterogeneity between studies was assessed using I2 and Cochran's Q tests. Begg's test was used to assess publication bias. Results Exposure to particulate matter less than 2.5 μm in diameter (PM2.5) (pooled effect = 1.73; 95%CI: 1.16~2.58; P <0.01), smoking history (pooled effect = 2.58; 95%CI: 2.00~3.32; P <0.01), passive smoking history (pooled effect = 1.39; 95%CI: 1.03~1.87; P = 0.03), male sex(pooled effect = 1.70; 95%CI: 1.31~2.22; P <0.01), body mass index (BMI) <18.5 kg/m2 (pooled effect = 1.73; 95%CI: 1.32~2.25; P <0.01), exposure to biomass burning emissions (pooled effect = 1.65; 95%CI: 1.32~2.06; P <0.01), childhood respiratory infections (pooled effect = 3.44; 95%CI: 1.33~8.90; P = 0.01), residence (pooled effect = 1.24; 95%CI: 1.09~1.42; P <0.01), and a family history of respiratory diseases (pooled effect = 2.04; 95%CI: 1.53~2.71; P <0.01) were risk factors for COPD in the Chinese population. Conclusion Early prevention of COPD could be accomplished by quitting smoking, reducing exposure to air pollutants and biomass burning emissions, maintaining body mass index between 18.5 kg/m2 and 28 kg/m2, protecting children from respiratory infections, adopting active treatments to children with respiratory diseases, and conducting regular screening for those with family history of respiratory diseases.